Վազգեն Ա Պալճյանը և Ռումինիայի «Հերկ» ամսագիրը (1937-1938 թթ.) - Լիլիթ Պողոսյան (ՀՀ ԳԱԱ հրատ.)
В статье освещается редакторская деятельность Вазгена I Палчяна в Румынии. В июне 1937 г. Карапет Палчян (позднее – католикос Вазген I Палчян) со своими товарищами по университету издает журнал “Герк” (“Пашня”), объем которого составлял 16 страниц большого формата. Редактором этого журнала становится именно он. This article considers Catholicos Vazgen I Palchyan’s editorial activities in Romania. Karapet Palchyan (later Catholicos Vazgen I Palchyan) with several patriot Armenian friends of the university founded “HERK” meaning ‘arable land’, a 16-paged monthly magazine in June 1937. He was the editor-in-chief as well as the editor-at-large of the magazine.
Keywords: Armenian Diaspora; Periodicals; Christianity; History of the Armenian Church; Biography